Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1112/jlms/jdp025
|View full text |Cite
|
Sign up to set email alerts
|

The Bergman property for semigroups

Abstract: In this article, we study the Bergman property for semigroups and the associated notions of cofinality and strong cofinality. A large part of the paper is devoted to determining when the Bergman property, and the values of the cofinality and strong cofinality, can be passed from semigroups to subsemigroups and vice versa.Numerous examples, including many important semigroups from the literature, are given throughout the paper. For example, it is shown that the semigroup of all mappings on an infinite set has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Recall from [15] that the Sierpiński rank of S, which we denote by SR(S), is the smallest integer n (if it exists) for which any countable subset of S is contained in an n-generated subsemigroup; if no such n exists, we say S has infinite Sierpiński rank and write SR(S) = ∞. Finally, following [21], we say that S has the semigroup Bergman property if the length function of S is bounded with respect to any generating set; that is, if for any generating set U of S we have S = U ∪ U 2 ∪ · · · ∪ U n for some n (which will typically vary, depending on the choice of U ). Clearly finite semigroups have finite Sierpiński rank (equal to the rank of the semigroup), and satisfy the semigroup Bergman property; it is in the setting of infinite semigroups that these notions become more interesting.…”
mentioning
confidence: 99%
“…Recall from [15] that the Sierpiński rank of S, which we denote by SR(S), is the smallest integer n (if it exists) for which any countable subset of S is contained in an n-generated subsemigroup; if no such n exists, we say S has infinite Sierpiński rank and write SR(S) = ∞. Finally, following [21], we say that S has the semigroup Bergman property if the length function of S is bounded with respect to any generating set; that is, if for any generating set U of S we have S = U ∪ U 2 ∪ · · · ∪ U n for some n (which will typically vary, depending on the choice of U ). Clearly finite semigroups have finite Sierpiński rank (equal to the rank of the semigroup), and satisfy the semigroup Bergman property; it is in the setting of infinite semigroups that these notions become more interesting.…”
mentioning
confidence: 99%
“…We prove that in the presence of a Katětov functor, additional mild assumptions ensure that the endomorphism monoid End(L) of the Fraïssé limit L is strongly distorted and its Sierpiński rank is at most five. Applying a result from [25], we conclude that if End(L) is not finitely generated, then it has the Bergman property. The constructions we present here are rather technical, and the reader might find it helpful to get acquainted with the constructions from [8] before going on.…”
Section: Semigroup Bergman Propertymentioning
confidence: 80%
“…Following [25], we say that a semigroup S is semigroup Cayley bounded with respect to a generating set U if S = U ∪ U 2 ∪ . .…”
Section: Semigroup Bergman Propertymentioning
confidence: 99%
“…Recall that a semigroup S has the semigroup Bergman property [34] if the length function of S is bounded with respect to any generating set for S. The property has this name since Bergman showed in [6] that an infinite symmetric group S X has the property. (Actually, Bergman showed that S X has this property with respect to group generating sets of S X , and the semigroup analogue was shown in [34,Corollary 2.5].…”
Section: Remark 39mentioning
confidence: 99%
“…The property is so named because of the seminal paper of Bergman [6], in which it was shown that the infinite symmetric groups have this property; in fact, Bergman showed that infinite symmetric groups have the corresponding property with respect to group generating sets, and the semigroup analogue was proved in [34]. Further studies have investigated the semigroup Bergman property in the context of other transformation semigroups [10,34,36].…”
Section: Introductionmentioning
confidence: 99%